2012
DOI: 10.1128/jb.00509-12
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the oprF Gene of Pseudomonas aeruginosa Is Dependent Mainly on the SigX Sigma Factor and Is Sucrose Induced

Abstract: The OprF porin is the major outer membrane protein of Pseudomonas aeruginosa. OprF is involved in several crucial functions, including cell structure, outer membrane permeability, environmental sensing, and virulence. The oprF gene is preceded by the sigX gene, which encodes the poorly studied extracytoplasmic function (ECF) sigma factor SigX. Three oprF promoters were previously identified. Two intertwined promoters dependent on 70 and SigX are located in the sigX-oprF intergenic region, whereas a promoter d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 57 publications
1
70
0
4
Order By: Relevance
“…In a previous study, Bouffartigues and colleagues demonstrated that in the P. aeruginosa strain PAO1, expression of the outer membrane porin OprF is dependent on SigX when the bacteria is cultivated in LB medium. The oprF gene is located 108 bp downstream of the sigX gene and was suggested before to be transcribed both monocistronically and bicistronically (10). Although we observed a slight downregulation of oprF in our PA14 sigX mutant (log 2 fold change of ÏȘ0.726; P Ï­ 0.075), oprF is not listed in our transcriptomic data (see Table S2 in the supplemental material) due to the stringent filter criteria.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…In a previous study, Bouffartigues and colleagues demonstrated that in the P. aeruginosa strain PAO1, expression of the outer membrane porin OprF is dependent on SigX when the bacteria is cultivated in LB medium. The oprF gene is located 108 bp downstream of the sigX gene and was suggested before to be transcribed both monocistronically and bicistronically (10). Although we observed a slight downregulation of oprF in our PA14 sigX mutant (log 2 fold change of ÏȘ0.726; P Ï­ 0.075), oprF is not listed in our transcriptomic data (see Table S2 in the supplemental material) due to the stringent filter criteria.…”
Section: Discussionmentioning
confidence: 46%
“…In P. aeruginosa deletion of sigX led to impaired growth under low-salt concentrations and reduced oprF expression (9). Later, Bouffartigues and colleagues confirmed these data and presented a link between lowered sodium chloride concentrations and the transcription of oprF due to the activation of the sigX promoter (10). As the ECF factor SigX was shown to be essential for survival under lowosmolarity-medium conditions and seems to be involved in responses to osmotic and cell wall stresses (9,10), it was suggested that the SigX regulon might be larger than anticipated.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Since bacterial outer membrane proteins (OMPs) play a crucial role in interaction of pathogens with immune cells (Confer and Ayalew, 2013), we determined the role of P. aeruginosa OprF in bacterial survival inside macrophages. OprF is the major OMP of P. aeruginosa and has been demonstrated to play an important role in interaction of this pathogen with host cells (Nestorovich et al, 2006; Bouffartigues et al, 2012; Reusch, 2012; Mishra et al, 2015). We observed that survival of otopathogenic P. aeruginosa inside macrophages requires bacterial oprF expression.…”
Section: Introductionmentioning
confidence: 99%